Project management Tools and Techniques (T&T) usage in building sector companies in Cartagena City, T.C.D.. (2019)
This research work was based on an analysis of project management tools and techniques usage and its practical application in the construction sector. It is a fact that projects currently have a high failure rate which was corroborated in this research work through a diagnosis carried out in the city of Cartagena to 22 project managers of important construction companies that currently execute housing projects and therefore, it was determined that techniques and tools of worldwide recognition and suggested by the most relevant standards and methodology are not being used in construction projects. In this work the deficiencies and strengths of the companies were shown when applying the project management techniques and tools; a guide was prepared to use them through specific recommendations to the construction sector. © 2019 Latin American and Caribbean Consortium of Engineering Institutions. All rights reserved.